Understanding the feasibility of home-based rehabilitation in kidney transplant recipients: A mixed-methods interpretation - Roseanne E. Billany; Hannah M. L. Young; Courtney J. Lightfoot; Nicolette C. Bishop; Alice C. Smith; Matthew P. M. Graham-Brown (PLoS ONE, 2025)
Background The ECSERT randomised controlled feasibility trial reported that a structured home-based exercise programme was feasible in kidney transplant recipients (KTRs). This study presents a qualitative evaluation of the trial and programme of exercise. The results are integrated and interpreted via a mixed methods analysis. Methods Fifty stable KTRs > 1-year post-transplant were randomised 1:1 to a 12-week home-based exercise programme or guideline-directed care control. Participants from the ECSERT trial intervention group ( n = 12) completed individual semi-structured interviews immediately and 3 months after the 12-week exercise programme. Interviews were analysed using reflexive thematic analysis. Quantitative data on feasibility (recruitment, adherence, and attrition) and qualitative data were collected concurrently, and combined using convergent mixed methods analysis with a joint display to further explore the primary feasibility findings. Results The mixed methods analysis facilitated the explanation and exploration of the successful feasibility findings. A key factor in recruitment was initial contact from a trusted healthcare professional. The benefits of additional health monitoring and the option to complete the programme later surpassed the disappointment of allocation to the control group. Key facilitators to exercise session completion were seeing change and preserving health, getting into a routine and the flexibility of home-based exercise, the variety of options, the importance of progression, the obligation to complete/being monitored, and the importance of support. At 3 months, many participants maintained some physical activity but described challenges with motivation, time, and illness. Conclusion Elements of the ECSERT trial design, trial procedures, and exercise programme that contributed to the successful feasibility of the main trial were identified. These results will allow researchers and practitioners to maximise the effectiveness of future trials and programmes of home-based exercise in KTRs.